Oxysterols in the Immune Response to Bacterial and Viral Infections - Cheng Xiang Foo; Stacey Bartlett; Katharina Ronacher (Cells, 2022)
Oxidized cholesterols, the so-called oxysterols, are widely known to regulate cholesterol homeostasis. However, more recently oxysterols have emerged as important lipid mediators in the response to both bacterial and viral infections. This review summarizes our current knowledge of selected oxysterols and their receptors in the control of intracellular bacterial growth as well as viral entry into the host cell and viral replication. Lastly, we briefly discuss the potential of oxysterols and their receptors as drug targets for infectious and inflammatory diseases.